2016
DOI: 10.1017/s0373463316000606
|View full text |Cite
|
Sign up to set email alerts
|

Maritime Route Delineation using AIS Data from the Atlantic Coast of the US

Abstract: This study examines maritime routes between ports along the Atlantic coast of the US, utilising Automated Identification System (AIS) data for the years 2010 through 2012. The delineation of vessel routes conducted in this study was motivated by development planned for offshore Wind Energy Areas (WEAs) along the Atlantic coast of the US and the need to evaluate the effect of these development areas on commercial shipping. To this end, available AIS data were processed to generate commercial vessel tracks for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…It also suggested that, where appropriate, route widths should encompass the lateral deviation associated with +/−2 standard deviations of the displacement of the traffic associated with movement between two locations. In [30], the difficulty of calculating smooth vessel routes and their accurate boundaries was identified by the authors, while adopting an approach which could deal with uncertainties and errors in the data. A convex hull is the smallest (w.r.t.…”
Section: Extracting the Global Network And Patterns Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…It also suggested that, where appropriate, route widths should encompass the lateral deviation associated with +/−2 standard deviations of the displacement of the traffic associated with movement between two locations. In [30], the difficulty of calculating smooth vessel routes and their accurate boundaries was identified by the authors, while adopting an approach which could deal with uncertainties and errors in the data. A convex hull is the smallest (w.r.t.…”
Section: Extracting the Global Network And Patterns Of Lifementioning
confidence: 99%
“…This work also focuses on a limited geographical region, specifically the Iberian Coast and the English Channel where network coverage is potentially good and there are few gaps in the dataset. In [30], Breithaupt et al, attempt to compute vessel routes between ports and to delineate route boundaries for a dataset covering the Atlantic coast of the US over a ten year time span. This approach resulted in continuous but not smooth boundaries that in some cases had boundary lines changing abruptly at transects.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions of various solutions to the problem of drafting trajectories for ships based on automatic identification system (AIS) historical data can be found in several publications (Anneken et al, 2015; Borkowski, 2017; Breithaupt et al, 2017; George et al, 2011; Lane et al, 2010; Ristic et al, 2008; Sang et al, 2016). The majority of them contain solely the results of the research, the main aims of which were to develop methods of detecting abnormalities and forecasting ship movement.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main research areas concerning AIS data: analysis of ship trajectories based on spatiotemporal attributes and statistical analysis based on other attributes. Analysis of ship trajectories is used for diverse purposes such as mapping shipping density for maritime situational awareness (Wu et al, 2016; MMO, 2013; Shelmerdine, 2015; Vettor and Soares, 2015; Fiorini et al, 2016), characterising marine traffic patterns (De Souza et al, 2016; Tsou, 2010; Iperen, 2015; Aarsæther and Moan, 2009; Chen et al, 2015; Altan and Otay, 2017; Breithaupt et al, 2017; Wang et al, 2017), anomaly detection (Pallotta et al, 2013; Zhang et al, 2016; Zhen et al, 2017; Ristic et al, 2008) and risk analysis (Zhou et al, 2013; Mou et al, 2010; Silveira et al, 2013; Mazaheri et al, 2015). An issue that these researchers have to deal with is cleaning raw AIS data, which is not easy, because of many erroneous AIS messages.…”
Section: Introductionmentioning
confidence: 99%